Low-Temperature Storage of Placenta Affects Anti-Inflammatory and Wound Healing Properties of its Extracts - Bobrova, Olena; Naumenko , Yevheniia; Shchetinskyi , Myroslav; Narozhnyi , Stanislav; Nardid , Оleg; Kalashnykova , Мarina; Shchetinska , Irina (Problems of Cryobiology and Cryomedicine, 2022)
Here we have studied the effect of low-temperature storage of the placenta at different temperatures on anti-inflammatory activity of its extracts in cell models of erythrocyte thermohemolysis and adenosine-5’-diphosphate-induced platelet aggregation. The wound-healing effect of cryopreserved placental extracts was also evaluated in rat thermal burn model. When preserving placenta for up to a month, the temperature of storage was shown to cause no significant impact on the percentage of inhibition of erythrocyte thermohemolysis and platelet aggregation by the extracts. Placental storage for three months at –20°C decreased anti-inflammatory activity of its extracts, and led to its complete loss during 6 months. Placental cryopreservation at –196°C enabled to preserve the anti-inflammatory and wound-healing activity. The cryopreserved placenta-derived extracts showed a pronounced positive effect on reparative process at third-degree (B) skin burn injury in rats. Probl Cryobiol Cryomed 2022; 32(2):144–157